THE EFFECT OF SERVICE, PRODUCT QUALITY, TRUST ON MEMBER SATISFACTION IN SHARIA MAWAR SAVES AND FINANCING COOPERATIVES (KSPP) - Silvia Karvika Putri; M. Rizal Nur Irawan; Kemal Farouq Mauladi (Sean Institute, 2023)
Cooperatives play an important role in the Indonesian economic system. In the current situation, competition between cooperatives is very tight and makes each cooperative compete to improve service, product quality, trust in the satisfaction of each member. This study aims to determine the effect of service, product quality, trust partially, simultaneously, and predominantly on member satisfaction. Meanwhile, the population used was 404 with a sample of 80 people. The data analysis methods are validity test, reliability test, classical assumption test (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), correlation test, coefficient of determination test, multiple linear regression test, t test and F test. In addition, based on the results of the study it can be seen that the product quality variable (X 2 ) has no partially significant effect on member satisfaction (Y) while the service variable (X 1 ) and trust variable (X 3 ) have a partially significant effect on member satisfaction (Y) with the results (X 1 ) t count = 3,679 > t table = 1,992, (X 2 ) t count = 1,251 < t table = 1,992, (X 3 ) t count = 3,469 > t table = 1.992. These three variables have a significant effect simultaneously on member satisfaction (Y) with the result of F count = 60.658 > F table = 2.72. Thus, regarding from those three variables, the service variable (X 1 ) has the highest value or is the most dominant of other variables. It can be concluded that partially the quality of the product quality variable (X 2 ) has no partially significant effect on member satisfaction (Y) while the service variable (X 1 ) and trust variable (X 3 ) have a partially significant effect on members satisfaction (Y). Meanwhile, the three variables simultaneously have a significant effect on member satisfaction (Y). So of the three variables that have a high value or the most dominant is the service variable (X 1 ).